Answer:
Option C.
Explanation:
Slope of the line passing through (1, 1) and (0, 2)
m =
![(y-y')/(x-x')](https://img.qammunity.org/2021/formulas/mathematics/middle-school/8j83nkrai4engwxwtfqllwolor1am9eitx.png)
m =
m = -1
Equation of the line passing through point (1, 1) and slope = -1,
y - y' = m(x - x')
y - 1 = (-1)(x - 1)
y - 1 = -x + 1
y = -x + 2
This piece of function is true for x ≤ 1
Similarly, slope of the line passing through two points (1, -1) and (2, -3),
m' =
![(-3+1)/(2-1)](https://img.qammunity.org/2021/formulas/mathematics/high-school/1kfm4cal5qsu25vndrcifsd71cfcxdszw9.png)
= -2
Equation of the line passing through (1, -1) and slope = -2
y + 1 = (-2)(x - 1)
y + 1 = -2x + 2
y = -2x + 1
This piece of function is true for x > 1
Therefore, Option C. will be the answer.